Pulmonary Inflammatory Myofibroblastic Tumor in Children: A Case Report and Brief Review of Literature - Camela, Federica; Gallucci, Marcella; di Palmo, Emanuela; Cazzato, Salvatore; Lima, Mario; Ricci, Giampaolo; Pession, Andrea (Frontiers in Pediatrics, 2018)
The inflammatory myofibroblastic tumor (IMT) is a rare lesion of unclear etiology and variable clinical course, consisting of a proliferation of fibroblasts and myofibroblasts, mixed with inflammatory cells. Synonyms of TMI are inflammatory pseudotumor and plasma cell granuloma reflecting the alleged inflammatory nature attributed to this lesion, even though this heterogeneity in the disease denomination is probably involved in a dispersion of the literature data. Among primary pulmonary neoplasms, it represents the most frequent endobronchial tumor of childhood and beyond the lung it has been described mainly in the bladder, mediastinum and mesentery. Despite having a tendency for local recurrence, the risk of distant metastasis is low. Clinical presentation depends on localization therefore lung peripheral lesions are often asymptomatic resulting in a delayed diagnosis. Radiological findings can suggest the diagnosis that must be confirmed by histopathology assessment. The tumor has been characterized by the application of immunohistochemical techniques, molecular biology and cytogenetics, which are very precious for the diagnosis. The therapeutic approach consists in the complete surgical excision of the lesion that normally ensures excellent survival. Due to the potential risk of recurrence, close clinical trial is indicated. To date only 24 cases of pulmonary IMT have been described, although the prevalence is probably higher. We present a case report of a 3 year old girl with pulmonary IMT and a brief review of known literature cases in order to highlight the most common clinical presentations, the most useful diagnostic tools and therapeutic approach.